Traditional Herbal Remedies used for the Treatment of Diabetes in South Eastern Region of Nepal - Singh, Shila (Tribhuvan University Journal, 2020)
Traditional knowledge has become recognized worldwide to control many diseases and diabetes is also one of them. In Nepal, remote areas are the root of the indigenous knowledge of medicinal plants. The present study aimed to record traditional medicinal uses of plants to control diabetes. Several times interactions were done with the traditional healers, local knowledgeable old person and other informants like few local people and household visits. A total of 39 plant species of 35 genera belonging to 23 angiosperm families were found to be used in diabetes. About 36 types of herbal remedies were investigated from the rural inhabitants of the area. These traditional recipes include extracts, leaves, powders, flour, seeds, vegetables, fruits and herbal mixtures. Traditional knowledge systems are culturally valued and scientifically important. Strengthening and disseminating the use -value of these plants can save the money and life of poor people.